Self-control problems and personalized regulation: Sin licenses revisited - Markus Haavio; Kaisa Kotakorpi (Aboa Centre for Economics (ACE), 2016)
We analyze personalized regulation in the form of sin licenses to correct the distortion in the consumption of a harmful good when consumers suffer from varying degrees of self-control problems. We take into account preference uncertainty, which generates a trade-off between flexibility and commitment provided by sin licenses. We also account for the possibility that consumers may trade the sin good in a secondary market, which partially erodes the commitment power of sin licenses. We show that if sophisticated consumers are allowed to choose any general, individualized pricing scheme for sin goods, they will choose a system of sin licenses. Nevertheless, sin licenses do not implement the social optimum in our general setting. We derive a simple criterion for assessing whether switching to a system of sin licenses improves welfare over linear sin taxes.
Keywords: H21; H30; I18; 330; self-control problems; sin licenses; non-linear pricing; demand uncertainty; secondary markets